TESTING OF B0, B30, B50, AND B100 ON LOW EMISSION VEHICLE EURO 4 - Kartika Putri, Agnes
The use of petroleum as fuel has many challenges which there is an imbalance between production capability and consumption rate of fossil fuels in Indonesia. In addition, the use of fossil diesel fuel has many negative influences to environment due to its exhaust emissions. Facing this problem, Indonesia, as a country that is very rich in palm oil, can use CPO (crude palm oil) to be processed into biodiesel as a substitute for fossil diesel fuel. This research aims to analyze and compare the effect of four different compositions of biodiesel and EURO 4 diesel fuel mixtures, namely B0, B30, B50, and B100 on exhaust gas emissions, fuel consumption and performance (power and torque). In addition, the author also formulated an empirical formula for the consumption of fuels B0, B30, B50, and B100 which were adjusted to the characteristics of each fuel using the carbon balance method. Tests which were carried out by Toyota Fortuner using Vehicle Test Cell (VTC) which consists of a chassis dynamometer and constant volume sampler (CVS). The emission results for B0, B30, B50, and B100 sequentially for CO emissions are 0.054 g/km, 0.029 g/km, 0.041 g/km, and 0.034 g/km, for HC emissions are 0.005 g/km, 0.001 g/km, 0.005 g/km, and 0.004 g/km, for NOx emissions are 0.239 g/km, 0.234 g/km, 0.252 g/km, and 0.382 g/km, for CO2 emissions are 242.664%, 244.52%, 248.32%, and 244.302%, and for particulates are 0.045 g/km, 0.033 g/km, 0.023 g/km, and 0.009 g/km. Fuel consumptions for B0, B30, B50, B100 respectively are 11 km/l, 11.04 km/l, 10.96 km/l, and 11.11 km/l. The empirical formulas for fuel consumption are obtained from the carbon balance method which need carbon mass fraction on fuel and emissions of HC, CO, and CO2. The formulas are validated by being compared with actual fuel consumption, which the errors obtained for B0, B30, B50, B100 are respectively 0.44 %, 1.75%, 1.36%, 2.42%.